Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Overexpression of PbWRKY66 negatively regulate phosphate uptake and root-to-shoot distribution in Arabidopsis - Mengdan Li; Wenyu Sun; Mengjie Wu; Fangyan Li; Zhen Cao; Nian Liu; Longjun Cheng (Plant Science, 2026)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Scalable flexible evaporator with enhanced thermal localization for solar driven water-power cogeneration - Longjun Wang; Xiquan Cheng; Xiao Sui; Jingwen Zhou; Zhuolin Han; Jingru Zhou; Guoke Zhang; Yingjie Zhang; Jun Ma; Kai Wang (Chemical Engineering Journal, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

The MPK6-LTF1L1 module regulates lignin biosynthesis in rice through a distinct mechanism from Populus LTF1 - Ping Zhu; Yu Zhong; Laifu Luo; Junhui Shen; Jiayan Sun; Laigeng Li; Longjun Cheng; Jinshan Gui (Plant Science, 2023)

Expressional characterization of galacturonosyltransferase-like gene family in Eucalyptus grandis implies a role in abiotic stress responses - Longjun Cheng; Xiaoxiang Ni; Mi Zheng; Lijuan Sun; Xiaofei Wang; Zaikang Tong (Tree Genetics & Genomes, 2018)

Genome-wide mining for microRNAs and their targets in Betula luminifera using high-throughput sequencing and degradome analyses - Junhong Zhang; Menghui Huang; Junsheng Liang; Ying Pan; Longjun Cheng; Jun Wu; Zaikang Tong (Tree Genetics & Genomes, 2016)